VICTORIA’S STRUGGLE FOR EQUALITY AS REFLECTED IN YOUNG VICTORIA THE MOVIE - YUANTI, SERLI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Woman Movement, Feminism, Woman Struggle, Early NineteenthCentury, Young Victoria Women movement is a women’s action to break down the patriarchy system which evolves in society. Women in early nineteenth century are different with women in modern era like now. Women in modern era tend to be more independent while women in early nineteenth century tend to be passive. This study examines women movement in early nineteenth century. Based on culture in that era, women and men have difference of right. They have different right of voting right, to decide their life choice and to get formal education. Women are not allowed to join formal education. Therefore, this study will examine the different right of women that shows in Young Victoria movie.This study uses feminism theory to know the women movement breaking down the patriarchy system in society and struggle their right in order to get the same right to men. Materialist feminism by Lois Tyson is used as the main theory. It states that women are free to choose their life to get their right. This theory is the appropriate theory to analyze the struggle of women to choose their career and life among the society. In addition to it, cinematography theory by Blain Brown and Gianetti are also applied to support the analysis of the visual image.This study reveals the women movement in the early nineteenth century in England which is done by a woman named Victoria, a Queen of England and the longest reigning British sovereign to date. Victoria has successes to break the patriarchy system. A patriarchy system is a system where men are in authority over women in all aspects of society and the position of women is under than men. In this case Victoria tries to break the patriarchy system to be independent and prove that women can be equal with men, women are not always as delicate and emotional creature, and women also can be tough and logical creature. Victoria’s actions do men’s activities such as play archery, chess and horse riding are her brave movements to break down the patriarchy system because we know that, women aren’t allowed to do that things because women are demanded not to do danger and brain activity. Victoria successfully breaks the stereotype that explains women as delicate and emotional creature to be tough, logical and brave creature by doing that activity.